L’utilizzo dei dispositivi wearables nello sport e nel fitness - Leone, Fabiana (Eracle. Journal of Sport and Social Sciences, 2018)
In recent years the use of technologies has significantly increased in sports, among the tools used are wearable devices. Considering some sporting and fitness practices in relation to the large and pervasive diffusion of the use of wearable devices allows highlighting some aspects of human phenomena. These phenomena, besides being able to be considered an expression of a more general trend of cultural order, highlight the emergence of a dimension of human identity that is particularly original and strongly linked to a specifically need for technological support in the definition of the self.